Public Policy and Local Development : An Analysis with Nepalese Perspective - Ghimire, Bhesh Raj (Humanities and Social Sciences Journal, 2023)
The intricate and significant relationship between local development and public policy is fundamental to understanding their interplay. Local development involves enhancing economic, social, and environmental conditions within specific geographic areas like cities, towns, or regions. In contrast, public policy encompasses the decisions, actions, and guidelines formulated by governments to address societal issues and achieve specific goals. Public policies essentially provide the framework and boundaries within which local development occurs. When well-crafted and effectively executed, public policies have the potential to catalyze positive outcomes in local development, fostering economic growth, improving quality of life, and enhancing overall community well-being. However, in Nepal, the execution of unsystematic policies for national development, along with local governments struggling to define their priorities and neglecting sustainable development based on local resources and job creation, presents a stark contrast to the ideal of local development as the foundation of democracy, reflecting the challenges and obstacles from the central to local government levels. Nepal should focus on sustainable development through the development policies for a self-reliant economy. This article tries to analyze the problems of public policies and local development.